Pengaruh Implementasi Enterprise Resource Planning (ERP) Apache Ofbiz Pada Kinerja UMKM Renyah.an - Jefril Rahmadoni; Putri Jugalo; Nadilla Saraswati; Muhammad Hafiz Aulia Rahmadoni; Salsabila Rahmah; Alvino Albas (Unversitas Muhammadiyah Riau, 2023)
The implementation of Enterprise Resource Planning (ERP) systems has become a priority for many organizations, including Micro, Small and Medium Enterprises (MSMEs) in the industrial sector. The purpose of this study was to evaluate the effect of Apache Ofbiz ERP implementation on performance of Renyah.an MSMEs. This research uses a descriptive qualitative approach to gain an in-depth understanding of the impact of ERP implementation on Renyah.an MSMEs Primary data was collected through interviews with Renyah.an's MSME owners and staff involved in ERP implementation. In addition, secondary data is also used to support the analysis. In this research, several indicators of organizational performance are used, including operational efficiency, customer satisfaction, and business growth. The results of this study indicate that the implementation of Apache Ofbiz ERP has a significant positive impact on the organizational performance of Renyah.an MSMEs. In terms of operational efficiency, ERP systems can increase productivity, reduce operational costs, and improve data accuracy. In addition, ERP implementation also has an impact on customer satisfaction by improving customer experience and increasing response time to customer requests. In terms of business growth, ERP implementation facilitates business expansion, better inventory monitoring, and more accurate data analysis for decision making.